Redox potential regulation toward suppressing hydrogen evolution in aqueous sodium-ion batteries: Na1.5Ti1.5Fe0.5(PO4)3. Issue 43 (17th October 2019) - Qiu, Yuegang; Yu, Yonghui; Xu, Jia; Liu, Yi; Ou, Mingyang; Sun, Shixiong; Wei, Peng; Deng, Zhi; Xu, Yue; Fang, Chun; Li, Qing; Han, Jiantao; et al.
Abstract : The redox potential regulation strategy effectively prevented the potential overlap between sodiation and hydrogen evolution in the charging process. Abstract : Aqueous sodium-ion batteries (ASIBs) show superior characteristics with high safety and low cost for large scale energy storage systems. However, easily occurring hydrogen evolution at a negative potential is a huge barrier to the application of anode materials in ASIBs. Even the most promising insert-type anode material, NaTi2 (PO4 )3 (NTP), cannot be commercialized due to its inadequate operating potential (−0.807 V vs. Ag/AgCl) that is close to the hydrogen evolution potential (−0.817 V vs. Ag/AgCl). Here, we report a redox potential regulation strategy to overcome this technical problem by integrating the redox couples of Ti 4+ /Ti 3+ and Fe 3+ /Fe 2+ to yield Na1.5 Ti1.5 Fe0.5 (PO4 )3 (NTFP) and increasing its operating potential up to −0.721 V vs. Ag/AgCl, which effectively prevents the potential overlap with the reductive decomposition of H2 O. Importantly, the excellent electrochemical properties and low energy consuming synthetic route to NTFP open a new perspective to energetically develop low cost and highly stable ASIBs as a large-scale energy storage tool.